FILTRATION DEVICES NOISES DURING ACUSTIC EMISSION SIGNALS DURING TUTNING ALUMINUM ALLOY - Девін, Л. М.; Найденко, А. Г.; Німченко, Т. В.; Чуйко, Ю. П. (Science-based technologies, 2009)
The methods of selection of acoustic emission signals in the presence of noises were shortly considered. The example of selection of acoustic emission signals on the background noise during the process of treatment of aluminium alloy was shown. The devices noise influence on the acoustic emission signal with use of the standard amplifying tract and the amplifier with differential entrances was determined.